Republic of Armenia : Staff Report for the 2006 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2006)
Armenia's economy continues to perform strongly. Prudent fiscal and monetary policies and ongoing structural reforms have contributed to double-digit growth in a low-inflation environment, a continued reduction in poverty, and a notable improvement in tax performance. The Poverty Reduction and Growth Facility (PRGF)-supported program is on track. Policy discussions centered around the appropriate monetary, exchange rate, and fiscal policy mix to maintain macroeconomic stability in the context of sizable foreign exchange inflows and on measures needed over the medium term to sustain and broaden economic growth.